Concurrent Infection of Influenza and COVID-19: A Review - Abrar Ahmad Zargar; Arvind Kumar; Ranjeet Kumar (International Journal of Virus Studies, 2024)
In December 2019, a novel coronavirus that causes respiratory illnesses was identified in Wuhan, China, and swiftly spread around the world. Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is a virus that spreads via the respiratory system and can cause pneumonia. Members of the Orthomyxoviridae family include influenza viruses. Although there are four genera in this family, influenza is only caused by genera A and B, which are clinically important for humans. Coinfection occurs when a person comes into touch with multiple viruses or infections at the same time. Regarding methods and processes of transmission, clinical features, and related immune reactions, SARS-CoV-2 is similar to influenza in a number of ways. Given the significance of the aforementioned co-infection and the approaching flu season, it is imperative to comprehend the similarities and differences between the immunopathogenesis, symptoms, and therapy of the flu virus and SARS-CoV-2. Both infections may cause pathological events and illnesses, including fever, inflammation, lymphopenia, coagulation, DIC (disseminated intravascular coagulation), gastrointestinal issues, elevated acute phase proteins (APPs), ARDS (acute respiratory distress syndrome), multi-organ failure, and mortality. So, we discussed over the flu-covid-19 coinfection, the similarities and differences, risk factors, virology, immunisations, and the immunological similarities and differences between influenza and COVID-19.
Keywords: COVID-19; Coinfection; Influenza; Sars-CoV-2; vaccinations; virology